Culinary risk register: A practical guide to open a culinary business - Suhendar, Bagus; Wahyuari, Wahyuari; Gustrian, Rachmadi (Universitas Malikussaleh, 2022)
This study aims to create a Culinary Risk Register (CRR) for prospective culinary entrepreneurs compiled based on the identification of the risks that exist in the culinary business. It is hoped that this CRR can be used as an alternative practical guide for those who want to open a culinary business, in order to mitigate the occurrence of business failures. The research method used is descriptive quantitative with 34 respondents. The indicators of the instruments were set up from the 4 risk categories, while Pareto Principal was use to analyse the data. The results is that there are 13 main risk factors which are necessary to be consider to open culinary business, out of 54 risk factors verified by the respondents. Among the 4 risk categories (financial, strategic, hazard, and operational risk), financial risk is the most prominent risk factor to be consider. There are two point that can be concluded from this research. Firstly, financial risk is the most prominent risk factor that must come into consideration in opening culinary business, among the others 3 risk categories. At the opening or existence stage is a critical phase, an entrepreneur is busy promoting the products, gathering and convincing customers, providing good service quality that will take some times before the entrepreneur can obtain regular customers as well as increase the number of new customers. A business failure and bankruptcy may happen anytime at this stage, if there is no well financial arrangement. It is quite recommended that a prospective entrepreneur must have adequate cash flow or sufficient capital and a projected cash flow of the business. Secondly, this research produces a list of culinary risks (CRR) which contains 13 risk factors that need to be considered in opening a culinary business.